2008
DOI: 10.1017/s1068280500002124
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors Affecting Weather- and Disease-Related Losses in the U.S. Farm-Raised Catfish Industry

Abstract: Two double-limit tobit models are used to identify significant risk factors that most affect farm-raised catfish losses from weather-related events and from disease outbreaks. Results of the weather loss model indicate that the variables for operator education level, number of ponds, pond water depth, production management strategy, past experience with severe losses from low oxygen levels from off-farm power outages, past experience with severe losses from diseases, and being in the South are statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…Mississippi Agriculture and Forestry Experiment Station researchers recommended that catfish ponds should have an average depth of 6-7 ft or 1.83-2.13 m (Coblentz 2003). Increased pond depth reduced nonspecific disease-related catfish losses (Hanson et al 2008). In contrast this study found greater pond depth increased the odds of a mortality event associated with columnaris disease.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Mississippi Agriculture and Forestry Experiment Station researchers recommended that catfish ponds should have an average depth of 6-7 ft or 1.83-2.13 m (Coblentz 2003). Increased pond depth reduced nonspecific disease-related catfish losses (Hanson et al 2008). In contrast this study found greater pond depth increased the odds of a mortality event associated with columnaris disease.…”
Section: Discussioncontrasting
confidence: 92%
“…Rebuilt ponds are deeper on these farms (Figure 2). A survey of catfish farmers found that the average pond depth in the southern region, including Alabama, Arkansas, Louisiana, and Mississippi, was 5.5 ft or 1.67 m (N = 553) (Hanson et al 2008). Mississippi Agriculture and Forestry Experiment Station researchers recommended that catfish ponds should have an average depth of 6-7 ft or 1.83-2.13 m (Coblentz 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature ranges of ESC outbreaks overlap the optimum temperature window of Ich infection at 22-24°C (Matthews, 2005;Dickerson, 2006). In 2002, 50.5% and 44.3% of all catfish operations (approximately 1000 total in the USA) had losses caused by ESC and by Ich (white spot), respectively (Hanson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since depth is a key component of volume (area × depth) this result in not unexpected. Hanson et al (2008) found that as pond depth increased, catfish losses from weather-related causes decreased, because the deeper ponds were not as sensitive to windstorms, droughts, and freezing. In contrast, Cunningham et al (2012) found that the incidence of columnaris increased as pond depth increased.…”
Section: Discussionmentioning
confidence: 99%